The Domestic Cat : The Biology of its Behaviour - Turner, Dennis C.; Bateson, Patrick (Cambridge : Cambridge University Press, 2013)
The most commonly kept domestic animal in the developed world, the cat has been a part of human life for thousands of years. Cats have been both worshipped and persecuted over this long period - either loved or hated for their enigmatic self-reliance and the subject of numerous myths and fables. Highlighting startling discoveries made over the last ten years, this new edition features contributions from experts in a wide range of fields, providing authoritative accounts of the behaviour of cats and how they interact with people. Thoroughly revised and updated to include information on the basic features of cat development and social life, the history of their relations with humans, health and welfare problems, and the breeding of cats for sale and for show. It is intended for all those, whether specialist or general reader, who love or are simply intrigued by these fascinating animals.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).